A European perspective on animal cloning and government regulation. - Galli, C. (IEEE Engineering in medicine and biology magazine)
The present situation in Europe can be described as the acceptance of the "precautionary" principle, by which any new biotech application is considered hazardous until proven safe beyond any possible doubt. This attitude is now so well established in the public opinion that it is very difficult for people to accept products (food in particular) that have been developed through biotech. People prefer traditional products, not because they are safer but because they were always there. For the reasons mentioned above, de facto there is no one significant European regulation on cloning, rather, every country has its own approach or variations.